CHARACTERIZATION OF EXPANDABLE CLAY MINERALS IN LAKE BAIKAL SEDIMENTS BY THERMAL DEHYDRATION AND CATION EXCHANGE - Grygar T.; Bezdicka P.; Hradil D.; Hruskova M.; Novotna K.; Kadlec J.; Pruner P.; Oberhansli H. (My University, 2005)
The sedimentary series from Academician Ridge, Lake Baikal, eastern Siberia, was examined using cation exchange capacity (CEC) to estimate the amount of expandable clay minerals (ECM) and high-temperature X-ray diffraction (HT-XRD) to determine their basic classification. The comparison of the magnetic susceptibility (MS) at sub-millennial resolution and the 18O record of a reference Atlantic core (ODP 980) was used to create an age model. The most closely studied part of the series covered the major part of the last glacial cycle (120−20 ky BP). The HT-XRD analysis is based on monitoring the course of ECM dehydration with 5°C steps between 25 and 250°C and enabled us to improve the discrimination between ECM, chlorite and micas. The CEC obtained at millennial resolution showed that the neoformation of ECM in warmer periods of the last interglacial was either insignificant or fully compensated by their dissolution or dilution. The CEC record was correlated with the main climatic stages in the period studied. Both MS and CEC records reflected the environmental changes at about millennial resolution, including climatic instabilities between 117 and 73 ky BP (late MIS5).